Recent Trends in Squamous Cell Carcinoma of the Anus Incidence and Mortality in the United States, 2001–2015. (19th November 2019) - Deshmukh, Ashish A; Suk, Ryan; Shiels, Meredith S; Sonawane, Kalyani; Nyitray, Alan G; Liu, Yuxin; Gaisa, Michael M; Palefsky, Joel M; Sigel, Keith
Abstract: Background: Squamous cell carcinoma of the anus (SCCA) incidence is rising in the United States. Study of incidence trends by stage at diagnosis, age-specific and birth cohort patterns, and trends in mortality could provide evidence for a true increase and etiological clues for the increase in incidence. Methods: Using the US Cancer Statistics dataset, we examined trends in SCCA incidence (2001–2015) and mortality (2001–2016) rates. Join-point regression was used to compute annual and average annual percentage change (AAPC). Incidence patterns by 5-year age group and birth cohort were evaluated using incidence rate ratios (IRRs) and age-period-cohort modeling. Results: SCCA incidence increased 2.7% per year (95% confidence interval [CI] = 2.1% to 3.3%), with pronounced increases in age groups 50 years and older. Distant-stage SCCA incidence tripled (AAPC = 8.6%, 95% CI = 5.4% to 12.0%, among men and AAPC = 7.5%, 95% CI = 4.8% to 10.2%, among women) and regional-stage SCCA incidence nearly doubled (AAPC = 4.7% for men and women) in both sexes; the AAPC for localized stage was 1.3% (95% CI = 0.6% to 2.0%) in men and 2.3% (95% CI = 1.8% to 2.8%) in women. Compared with adults born circa 1946, recently born black men (born circa 1986) had a nearly fivefold higher risk (IRR = 4.7, 95% CI = 2.1 to 10.2) of SCCA, and the risk doubled among white men (IRR = 2.0, 95% CI = 1.7 to 2.2) and white women (IRR = 2.1, 95% CI = 1.9 to 2.3) born after circa 1960. Anal cancer mortality rates increased 3.1% per year (95% CI = 2.6% to 3.5%) with statistically significant increases in age groups 50 years and older. SCCA incidence-based mortality increased 1.9% annually (95% CI = 0.5% to 3.4%), with a notable (4.9%, 95% CI = 2.4% to 7.3%, per year) rise in adults ages 60–69 years. Conclusion: The increase in SCCA incidence, particularly advanced-stage disease, and a similar increase in mortality suggest a true increase in the occurrence of SCCA. Future research and improved prevention are urgently needed to mitigate the increasing disease burden.